A representação da informação do custo no processo de projeto arquitetônico - Ribeiro, Letícia Pereira Barcelos (2024)
Representing information is a way to facilitate the understanding of something that, otherwise, would not be possible or would be very difficult to achieve. In this sense, this research focuses on investigating how to represent cost information throughout the architectural project to support decision-making. To achieve this, three main aspects will be considered: the first aspect is the Level of Development (LOD) of an architectural project, the second is the cost estimation of a project, and finally, the third is the use of Building Information Modeling (BIM) as a facilitator in the relationship between the first and the second. The general objective of the research is to facilitate the visualization of building cost estimates during the conception and development of the architectural project, thereby providing greater support for design decision- making. In order to achieve this, the applied methodology is Design Science Research (DSR), as this research aims to propose an artifact grounded in theory but also practical enough to contribute to the chosen theme. The research was conducted following the DSR-oriented phases: awareness of the problem, suggestion, development, evaluation, and results. As a theoretical contribution, a conceptual model was developed that relates levels of development in the architectural design process, project cost estimation, and BIM parameters. As a practical contribution, a tool was developed that integrates information modeling with a visual programming interface (VPI) throughout the design process, focusing on cost information visualization in the early stages of the project and aimed at residential typology. To evaluate the tool, it was instantiated by applying it in educational experiences and with a focus group to verify its potential results in a real environment.